Optimasi Sarana dan Prasarana dalam Implementasi Kurikulum Nasional di Sekolah Menengah Pertama di Indonesia: Optimization of Facilities and Infrastructure in the Implementation of the National Curriculum in Junior High Schools in Indonesia - Khasanah, FItri Uswatun; Jumintono (Pendidikan Al-Gafari, 2025)
The utilization of classroom facilities and infrastructure is a fundamental element in creating a conducive learning environment, especially at the secondary education level. However, in many semi-urban public schools in Indonesia, the optimization of learning facilities remains unfulfilled due to limitations in distribution, management, and maintenance. This study aims to explore how classroom facilities are used to support the learning process at public junior high schools in Sragen Regency and to identify adaptive practices that emerge in response to these limitations. This research employed a qualitative approach using a case study design. Data collection techniques included direct observation, semi-structured interviews with subject teachers, homeroom teachers, the head of facilities and infrastructure, and students, as well as documentation through photographs, field notes, and school records. Data were analyzed using the interactive model by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that blackboards were consistently used in all teaching sessions (100%), while projectors were used in 80% of sessions but were frequently affected by technical disruptions. The classroom layout was generally flexible, although some desks and chairs were damaged. Ventilation and lighting in several classrooms did not meet optimal standards. Teachers’ ad-hoc innovations and limited community involvement in facility maintenance were also identified. These findings underscore the importance of strengthening facility governance, teacher training, and collaboration with communities and external partners to build an inclusive, adaptive, and sustainable learning environment.